In Vitro Global Gene Expression Analyses Support the Ethnopharmacological Use of Achyranthes aspera. (15th December 2013) - Subbarayan, Pochi R.; Sarkar, Malancha; Nathanson, Lubov; Doshi, Nikesh; Lokeshwar, Balakrishna L.; Ardalan, Bach
Abstract : Achyranthes aspera (family Amaranthaceae ) is known for its anticancer properties. We have systematically validated the in vitro and in vivo anticancer properties of this plant. However, we do not know its mode of action. Global gene expression analyses may help decipher its mode of action. In the absence of identified active molecules, we believe this is the best approach to discover the mode of action of natural products with known medicinal properties. We exposed human pancreatic cancer cell line MiaPaCa-2 (CRL-1420) to 34  μ g/mL of LE for 24, 48, and 72 hours. Gene expression analyses were performed using whole human genome microarrays (Agilent Technologies, USA). In our analyses, 82 (54/28) genes passed the quality control parameter, set at FDR ≤ 0.01 and FC of ≥±2. LE predominantly affected pathways of immune response, metabolism, development, gene expression regulation, cell adhesion, cystic fibrosis transmembrane conductance regulation (CFTR), and chemotaxis (MetaCore tool (Thomson Reuters, NY)). Disease biomarker enrichment analysis identified LE regulated genes involved in Vasculitis—inflammation of blood vessels. Arthritis and pancreatitis are two of many etiologies for vasculitis. The outcome of disease network analysis supports the medicinal use of A. aspera, viz, to stop bleeding, as a cure for pancreatic cancer, as an antiarthritic medication, and so forth.